Potrayal of women's art work and traditional attire in National Heritage Museum Pakistan & National Textile Museum Malaysia - Awan, Haram; Rehman, Adeela; Fathil, Fauziah (Patridge Publishing, 2018)
Traditionally, a museum is an asset as it contains a tremendous amount of history. It helps people to understand various aspects of an area’s tradition, culture and custom and keeps the history alive. It is an important source of history to guide us into the future. Currently, there is very weak connection between new generations and their cultural heritage which has been practised by their ancestors. Museums can bridge this gap and rebuild the decaying relationship through cultural interpretation of the artefacts with community support.With regard to the role of women, museums play a vital role in making the work of women visible in folk culture, as they depict the culture of different regions. The focus of the present study is on the visibility of women’s work in folk culture museum or more specifically, the relationship between cultural museum with contributions of women in folk culture; therefore, the objectives of this research are to explore the role of museums in promoting women’s work, to know about such work which are being depicted in museums and to explore women’s traditional and changing roles as highlighted in museums.